N-Cadherin and Integrin Blockade Inhibit Arteriolar Myogenic Reactivity but not Pressure-Induced Increases in Intracellular Ca2+ - Jackson, Teresa Y.; Sun, Zhe; Martinez-Lemus, Luis A.; Hill, Michael A.; Meininger, Gerald A. (Frontiers in Physiology, 2010)
The vascular myogenic response is characterized by arterial constriction in response to an increase in intraluminal pressure and dilatation to a decrease in pressure. This mechanism is important for the regulation of blood flow, capillary pressure and arterial pressure. The identity of the mechanosensory mechanism(s) for this response is incompletely understood but has been shown to include the integrins as cell-extracellular matrix receptors. The possibility that a cell-cell adhesion receptor is involved has not been studied. Thus, we tested the hypothesis that N-cadherin, a cell-cell adhesion molecule in vascular smooth muscle cells (VSMCs), was important for myogenic responsiveness. The purpose of this study was to investigate: 1. whether cadherin inhibition blocks myogenic responses to increases in intraluminal pressure and 2. the effect of the cadherin or integrin blockade on pressure-induced changes in [Ca2+]i. Cadherin blockade was tested in isolated rat cremaster arterioles on myogenic responses to acute pressure steps from 60 – 100 mmHg and changes in VSMC Ca2+ were measured using fura-2. In the presence of a synthetic cadherin inhibitory peptide or a function blocking antibody, myogenic responses were inhibited. In contrast, during N-cadherin blockade, pressure-induced changes in [Ca2+]i were not altered. Similarly, vessels treated with function-blocking β1- or β3-integrin antibodies maintained pressure-induced [Ca2+]i responses despite inhibition of myogenic constriction. Collectively, these data suggest that both cadherins and integrins play a fundamental role in mediating myogenic constriction but argue against their direct involvement in mediating pressure-induced [Ca2+]i increases.